2019
DOI: 10.3390/app10010280
|View full text |Cite
|
Sign up to set email alerts
|

The Implicit Keller Box Scheme for Combined Heat and Mass Transfer of Brinkman-Type Micropolar Nanofluid with Brownian Motion and Thermophoretic Effect Over an Inclined Surface

Abstract: The main purpose of the present analysis is to report the numerical solution of the thermal radiations and magnetohydrodynamic (MHD) effect on the flow of micropolar nanofluid. Further, the effect of Brownian motion and thermophoresis on the flow field are also elucidated. The combined phenomenon of heat and mass transfer is considered. Compatible similarities are implemented for the conversion of nonlinear ordinary differential equations from nonlinear partial differential equations. The numerical solution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Srinivasacharya et al [26] explored the double diffusive effect on the flow of micropolar fluid on a slanted sheet. Other similar studies on the different aspects of fluids are given in [27][28][29][30][31]. The flow symmetry of fluids in general has been studied using theoretical methods, various experiment methods, and different numerical techniques, in various fields such as the field of fluid mechanics, the field of thermal engineering, etc., due to their several benefits and relevance in terms of flow control and heat transfer enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…Srinivasacharya et al [26] explored the double diffusive effect on the flow of micropolar fluid on a slanted sheet. Other similar studies on the different aspects of fluids are given in [27][28][29][30][31]. The flow symmetry of fluids in general has been studied using theoretical methods, various experiment methods, and different numerical techniques, in various fields such as the field of fluid mechanics, the field of thermal engineering, etc., due to their several benefits and relevance in terms of flow control and heat transfer enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies on convective flows in porous media were surveyed in the books by Nield and Bejan [20] and Ingham and Pop [21,22]. Although several studies have been discussing the thermophoretic effect on convection flow, or fluid flow over porous media in the literature [23][24][25][26][27][28][29][30], there is still a lack of published papers probing natural convective flow through a porous medium with heat and mass transfer rates for a low Schmidt number under variable wall heat fluxes. Commonly, the air pollution substance comes from aerosol particles and toxic gaseous molecules with low Schmidt numbers, such as hydrocarbons or sulfur dioxide (SO 2 ).…”
Section: Introductionmentioning
confidence: 95%
“…In their analysis the authors observed 6.35% efficiency in the Nusselt number against MoS 2 nanoparticulate. The behavior of the Brinkman-type micropolar nanofluid motion in response of thermal radiation and nanoparticles is examined by Rafique et al 27 . The authors obtained the solution of the assumed phenomena via numerical method i.e., Keller box technique.…”
Section: Introductionmentioning
confidence: 99%